Determinants of Company Value in Earnings Management Moderation - Hentin, Novriella EnoRehita Kharisma; Sari, Ati Retna; Setyowati, Supami Wahyu (IJBLE Scientific Publications Community Inc., 2025)
This study aims to analyze whether profitability, liquidity, and company size affect company value, considering earnings management, in manufacturing companies within the food and beverage sub-sector listed on the Indonesia Stock Exchange for the period 2021-2024. The sample for this study was taken using purposive sampling, resulting in 17 companies that met the research criteria. The analysis technique used classical assumption testing and moderated regression analysis using SPSS. Hypothesis testing involved multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination. The analysis results indicate that profitability has a positive and significant impact on company value, whereas liquidity and company size do not have a significant effect on company value. In accordance with the t-test results, profit management moderates the relationship between profitability and company value, but is unable to moderate the relationships between liquidity and company size and company value.